Biogenic silver nanoparticles eradicate of Pseudomonas aeruginosa and Methicillin-resistant Staphylococcus aureus (MRSA) isolated from the sputum of COVID-19 patients - Hawsawi, Nahed M.; Hamad, Arshad M.; Rashid, Sahar N.; Alshehri, Fatma; Sharaf, Mohamed; Zakai, Shadi A.; Al Yousef, Sulaiman A.; Ali, Ahmed Mohamed; Abou-Elnour, Amira; Alkhudhayri, Abdulsalam; Elrefaei, Nadia Gouda; Elkelish, Amr (Frontiers in Microbiology, 2023)
In recent investigations, secondary bacterial infections were found to be strongly related to mortality in COVID-19 patients. In addition, Pseudomonas aeruginosa and Methicillin-resistant Staphylococcus aureus (MRSA) bacteria played an important role in the series of bacterial infections that accompany infection in COVID-19. The objective of the present study was to investigate the ability of biosynthesized silver nano-particles from strawberries (Fragaria ananassa L.) leaf extract without a chemical catalyst to inhibit Gram-negative P. aeruginosa and Gram-positive Staph aureus isolated from COVID-19 patient's sputum. A wide range of measurements was performed on the synthesized AgNPs, including UV–vis, SEM, TEM, EDX, DLS, ζ -potential, XRD, and FTIR. UV-Visible spectral showed the absorbance at the wavelength 398 nm with an increase in the color intensity of the mixture after eight hours passed at the time of preparation con-firming the high stability of the FA-AgNPs in the dark at room temperature. SEM and TEM measurements confirmed AgNPs with size ranges of ~40-~50nm, whereas the DLS study confirmed their average hydro-dynamic size as ~53 nm. Furthermore, Ag NPs. EDX analysis showed the presence of the following elements: oxygen (40.46%), and silver (59.54%). Biosynthesised FA-AgNPs (ζ = ˗17.5±3.1 mV) showed concentra-tion-dependent antimicrobial activity for 48 hours in both pathogenic strains. MTT tests showed concentra-tion-dependent and line-specific effects of FA-AgNPs on cancer MCF-7 and normal liver WRL-68 cell cul-tures. According to the results, synthetic FA-AgNPs obtained through an environmentally friendly biological process are inexpensive and may inhibit the growth of bacteria isolated from COVID-19 patients.